2013
DOI: 10.1111/apt.12279
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: pentoxifylline for the treatment of severe alcoholic hepatitis

Abstract: SUMMARY BackgroundAcute alcoholic hepatitis (AH) is a severe manifestation of alcoholic liver disease with a grave prognosis. Pentoxifylline, an oral antitumour necrosis factor agent, has been reported to reduce mortality and incidence of hepatorenal syndrome (HRS) in severe alcoholic hepatitis (SAH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 36 publications
2
52
1
3
Order By: Relevance
“…5,6,11 Along the same accord, a recent meta-analysis of pentoxifylline demonstrated a decreased incidence of fatal HRS but no short-term survival benefit compared to placebo. 12 Lack of survival benefit was most recently described by Thursz and colleagues in the STOPAH trial, which evaluated the effects of prednisolone and pentoxifylline therapy in 1103 severe AH patients with higher average MDF scores in the treatment group compared to our study (MDF = 63 in STOPAH vs. MDF = 42 in our study). The STOPAH investigators found that while prednisolone was associated with a non-significant reduction in mortality, neither steroid (14% treatment vs. 18% non-treatment, P = 0.06) nor pentoxifylline (16% treatment vs. 16% non-treatment, P = 0.69) were effective in reducing 28-day mortality.…”
Section: Discussionmentioning
confidence: 43%
“…5,6,11 Along the same accord, a recent meta-analysis of pentoxifylline demonstrated a decreased incidence of fatal HRS but no short-term survival benefit compared to placebo. 12 Lack of survival benefit was most recently described by Thursz and colleagues in the STOPAH trial, which evaluated the effects of prednisolone and pentoxifylline therapy in 1103 severe AH patients with higher average MDF scores in the treatment group compared to our study (MDF = 63 in STOPAH vs. MDF = 42 in our study). The STOPAH investigators found that while prednisolone was associated with a non-significant reduction in mortality, neither steroid (14% treatment vs. 18% non-treatment, P = 0.06) nor pentoxifylline (16% treatment vs. 16% non-treatment, P = 0.69) were effective in reducing 28-day mortality.…”
Section: Discussionmentioning
confidence: 43%
“…However, other studies found contrasting results and meta-analysis has failed to show any significant benefit of this drug. [19][20][21] Although published evidence for the use of PTX is inconclusive, the drug is widely used as an alternative to steroids, particularly in the USA, and further evaluation in a clinical trial is, therefore, clearly warranted.…”
Section: Pentoxifyllinementioning
confidence: 99%
“…However, two meta-analyses have not shown any convincing benefit associated with pentoxifylline. 11,12 Two small studies have compared glucocorticoids with pentoxifylline, but the results were inconsistent. 13,14 Two other studies have compared the effect of glucocorticoid monotherapy with that of combined treatment with glucocorticoids and pentoxifylline but showed no benefit from the addition of pentoxifylline.…”
Section: In a 2008mentioning
confidence: 99%